Modulation of Glutathione Hemostasis by Inhibition of 12/15-Lipoxygenase Prevents ROS-Mediated Cell Death after Hepatic Ischemia and Reperfusion. (24th July 2017) - Drefs, Moritz; Thomas, Michael N.; Guba, Markus; Angele, Martin K.; Werner, Jens; Conrad, Marcus; Steib, Christian J.; Holdt, Lesca M.; Andrassy, Joachim; Khandoga, Andrej; Rentsch, Markus
Abstract : Background . Reactive oxygen species- (ROS-) mediated ischemia-reperfusion injury (IRI) detrimentally impacts liver transplantation and resection. 12/15-Lipoxygenase (12/15-LOX), an antagonistic protein of the glutathione peroxidase 4 (GPX4) signaling cascade, was proven to mediate cell death in postischemic cerebral and myocardial tissue. The aim of this study was to investigate the impact of 12/15-LOX inhibition on hepatic IRI. Methods . Livers of C57BL/6 mice were exposed to 60 minutes of partial warm ischemia and 90 minutes of reperfusion after previous Baicalein administration, an inhibitor of 12/15-LOX. Tissue samples were analyzed by TUNEL assay, Western blot, and spectral photometry. Results . TUNEL labeling showed a significant reduction of hepatic cell death following baicalein pretreatment. Western Blot analysis revealed a significant downregulation of Jun-amino-terminal-kinase (JNK), caspase-3, and poly-ADP-ribose-polymerase (PARP), besides considerably lowered p44/42-MAP-kinase (ERK1/2) expression after Baicalein administration. A significant elevation of glutathione oxidation was measured in Baicalein pretreated livers. Conclusion . Our data show that inhibition of 12/15-lipoxygenase causes significant cell death reduction after hepatic ischemia and reperfusion by enhancing glutathione metabolism. We conclude that GPX4-dependent cell death signaling cascade might play a major role in development of hepatic IRI, in which the investigated proteins JNK, caspase-3, ERK1/2, and PARP might contribute to tissue damage.